Guidelines for clinical trials of frontal fibrosing alopecia: consensus recommendations from the International FFA Cooperative Group (IFFACG). (13th August 2021) - Olsen, E. A.; Harries, M.; Tosti, A.; Bergfeld, W.; Blume‐Peytavi, U.; Callender, V.; Chasapi, V.; Correia, O.; Cotsarelis, G.; Dhurat, R.; Dlova, N.; Doche, I.; et al.
Summary: Background: Frontal fibrosing alopecia (FFA) has become one of the most common causes of cicatricial alopecia worldwide. However, there is a lack of clear aetiology and robust clinical trial evidence for the efficacy and safety of agents currently used for treatment. Objectives: To enable data to be collected worldwide on FFA using common criteria and assessment methods. Methods: A multicentre, international group of experts in hair loss was convened by email to create consensus recommendations for clinical trials. Consensus was defined at > 90% agreement on each recommended part of these guidelines. Results: Standardized diagnostic criteria, severity rating, staging, and investigator and patient assessment of scalp hair loss and other clinical features of FFA were created. Conclusions: These guidelines should allow the collection of reliable aggregate data on FFA and advance efforts in both clinical and basic research to close knowledge gaps in this condition. Abstract : What is already known about this topic? Frontal fibrosing alopecia (FFA) is a common psychologically debilitating progressive type of hair loss without a clear aetiology or treatments vetted by well‐controlled clinical trials. What does this study add? This paper provides methods for collecting meaningful data on FFA in clinical trials, databases and registries across the globe. These guidelines will promote clinical and basic research on well‐defined populations of patients affected with FFA and provide the means to assess the efficacy and safety of individual treatments. Linked Comment: M. Kinoshita‐Ise. Br J Dermatol 2021; 185 : 1092–1093 . Plain language summary available online